Anti-HBs Antibodies over time in healthcare workers - Sharma, Tanishka; Mittal, Garima; Kalra, Charu; Agarwal, Rajiv Kumar; Rawat, Balwant S (Indian Journal of Community Health, 2019)
Background: In developing countries including India only 18 % HCWs are vaccinated against HBV. Inspite of all the recommendations, compliance to vaccination remain poor in majority of health care settings. Aims & Objectives: To estimate serum levels of anti-HBs antibodies in healthcare workers and to correlate the values of Anti-HBs level over time in health care workers. Materials and Methods: This cross-sectional study was conducted on Health care workers of tertiary care hospital. Their demographic details and hepatitis B vaccination history was recorded as per performa. Serum samples of all the subjects were tested for Anti-HBs levels by VIDAS-PC equipment. Results: Out of the 294 HCWs enrolled, 84% (247) were fully vaccinated whereas 16%(47) were partially vaccinated. The vaccination rate was highest among nursing staff (74.9%) followed by doctors (13.8%). 3% of doctors and 12.4% of nurses are still at risk of acquiring HBV infection. On anti -HBs titer estimation, 9.7% of the HCWs had anti-HBs titer < 10 mIU/ml while 90.3% had titre > 10 mIU/ml. Conclusion: This study demonstrated that Hepatitis B immunization must be made compulsory for hospital staff in every health care setting as well as to check their anti HBs titres.